Strategi Pendekatan Konsultatif Financial Consultant dalam Mendorong Literasi dan Kepercayaan Investasi di Perusahaan Pialang - Labib Zuwitanto, Moch; Kurniasari, Irma (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The role of financial consultants in brokerage firms has shifted from being mere product sellers to strategic partners for clients. This community service journal explores in depth the consultative approach strategy implemented by financial consultants in guiding prospective and existing clients in brokerage firms. Through this approach, the main focus is on building understanding, trust, and providing truly personalized investment solutions, rather than just being sales-oriented. Participatory observation methods and case study analysis are used to identify the stages, key skills, and impacts of the consultative approach on increasing public investment literacy and client satisfaction. The results of this activity show an increase in participants' knowledge of investment instruments and growth in confidence in making wiser investment decisions. The consultative approach has proven effective in bridging the information gap between industry players and the general public.